2009
DOI: 10.1103/physrevlett.102.048101
|View full text |Cite
|
Sign up to set email alerts
|

Thermal (In)Stability of Type I Collagen Fibrils

Abstract: We measured the Young's modulus at temperatures ranging from 20 to 100 degrees C for a collagen fibril that is taken from a rat's tendon. The hydration change under heating and the damping decrement were measured as well. At physiological temperatures 25 to 45 degrees C, the Young's modulus decreases, which can be interpreted as an instability of the collagen. For temperatures between 45 and 80 degrees C, the Young's modulus first stabilizes and then increases when the temperature is increased. The hydrated wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…The calculation assumes the typical ∼1000 residue per individual polypeptide chain in a triple helix and a dermal collagen content of 80%. This range of absorbed water is slightly lower, but generally consistent with Gevorkian et al,29 where water content in rat tail tendon at 93% RH was reported at ∼2 mol H 2 O/mol amino acid and the hydration networks of 1–3 mol H 2 O/mol amino acid revealed in x‐ray diffraction studies of collagen‐like peptides 2, 30, 31…”
Section: Resultssupporting
confidence: 88%
“…The calculation assumes the typical ∼1000 residue per individual polypeptide chain in a triple helix and a dermal collagen content of 80%. This range of absorbed water is slightly lower, but generally consistent with Gevorkian et al,29 where water content in rat tail tendon at 93% RH was reported at ∼2 mol H 2 O/mol amino acid and the hydration networks of 1–3 mol H 2 O/mol amino acid revealed in x‐ray diffraction studies of collagen‐like peptides 2, 30, 31…”
Section: Resultssupporting
confidence: 88%
“…This effect was first found in Ref. [18]; it was argued to be related to formation of inter-molecular bonds between partially denaturated fibril constituents. Note that the denaturation temperature of collagen tendon, as measured calorimetrically, is also located around 60 − 70 C when heating under speed larger than 1 C/min [13][14][15][16].…”
mentioning
confidence: 72%
“…5,6 show that when heating at speed 1 C/min the collagen fibril undergoes softening transition at temperatures around T soft = 70 C, where θ has a sharp maximum. We note however that the behavior of the Young's modulus E is more intricate [18] than during the glass transitions in synthetic polymers, e.g., rosin [9,10]. It is seen that for T < T soft , E decreases upon increasing T ; this is a typical scenario for the softening transition.…”
mentioning
confidence: 99%
“…The axial structure is long-range ordered, but it also contains relatively disordered units [1] , [27] . Laterally, the fibril is an approximately hexagonal microcrystal; the range of the lateral order is much less than the axial order range [26] . Fibrils and microfibrils are stabilized by several different factors: a small number of covalent links between terminal points of collagen triple-helices, carbonyl-water hydrogen-bonds, hydrophobic and van der Waals interaction between triple-helices, etc [1] , [2] .…”
Section: Materials and Experimental Methodsmentioning
confidence: 99%